WORKING, SAFETY AND HEALTH CONDITIONS IN THE ECONOMICALLY ACTIVE AND EMPLOYED POPULATION IN URBAN AREAS OF PERU. - Sabastizagal-Vela, Iselle; Astete-Cornejo, Jonh; G. Benavides, Fernando (Revista Peruana de Medicina Experimental y Salud Pública, 2020)
Objetives: The present study aims to know the work, safety and health conditions at the jobs of the economically active urban population in Peru. Materials and Methods: A cross-sectional study was carried out based on a probabilistic sample of multistage areas in which 3122 people over 14 years of age distributed nationwide participated. Results: The majority were men (53.6%) between 30 and 59 years (50%). As for working conditions, most people work more than 48 hours per week (39.8%), and Monday through Saturday (44.7%). Regarding the safety, hygiene, ergonomic and psychosocial conditions, the results showed a lower risk exposure. Regarding health conditions, the majority report that the identification and evaluation of occupational hazards is not carried out in their workplace (35.9%), they do not have occupational health services (40.7%) or a delegate or a Health and safety committee (39.4%) and no occupational medical evaluations (39.3%). Conclusions: The economically active urban population of Peru is more frequently exposed to noise, solar radiation, awkward postures and repetitive movements, work at a fast pace with little control and hide their emotions; In addition, occupational health is not managed adequately in workplaces. These conditions may affect the health of workers and the quality of work.